The Effect of Hormonal Contraceptive use on Breast Milk Production in Breastfeeding Mothers at Meurah Mulia Health Center, North Aceh Regency - Lina Ekawati; Thomson Nadapdap; Aida Fitria (Universitas Ibn Khaldun Bogor, 2024)
This study aims to determine the effect of using hormonal contraception on breast milk production in breastfeeding mothers at the Meurah Mulia Health Center, North Aceh Regency in 2023. The research was conducted with a retrospective case-control design. The results of the analysis show that the use of hormonal contraception has a significant effect on breast milk production in breastfeeding mothers (p=0.017; OR=2.269), where mothers who use hormonal contraception are twice as likely to have less breast milk production compared to mothers who use non-hormonal contraception. In conclusion, this research shows that there is an influence of the use of hormonal contraception on breast milk production in breastfeeding mothers, so it is recommended that health services provide sufficient information to women who want to use contraception, especially women who are breastfeeding, regarding the effect of contraception on breast milk production.